Informal healthcare providers of abortion services among three scheduled tribes of Jharkhand - Ujjwala Gupta (Wolters Kluwer Medknow Publications, 2023)
Background: There is a dominant role of informal healthcare providers (IHPs) in the current cultural and sociological context of tribal communities. They outnumber formal health-care providers, thus bridging the gap between existing and nonexisting public health facilities despite not having formal training or accreditation. Objectives: The study examines the role, relevance, and extent of abortion services provided by IHPs- in Jharkhand among three Scheduled Tribe groups. Materials and Methods: Based on in-depth interviews with 15 IHPs and 42 married women among three Scheduled Tribe groups in three districts of Jharkhand, a qualitative study was conducted. Interview guidelines addressed reasons for preferring IHP services, their scope of practice, dissemination, and quality of services. Results: The majority of women seeking abortions used traditional contraceptives, which often resulted in unwanted pregnancies. The economic, cultural, social, access to services, and confidence factors encouraged women to seek abortion services from IHPs. There were differences in the nature of access to abortion services among tribal groups. The Chero and Korwa tribes continued to rely heavily on simpler life technologies that shaped their beliefs and practices regarding reproduction. The Ho tribe, however, preferred to use the formal health-care system since they were close to a more complex society. Conclusion: IHP plays a significant role in the social structure of Tribes, demonstrating their marginalization in access to formal health-care services. Eventually, they replaced traditional healers with their function as physicians.